Medien und Minderheiten - Kriwak, Andreas; Pallaver, Günther (innsbruck university press, 2012)
The interdisciplinary research area innsbruck media studies at the University of Innsbruck aims at understanding, explaining and designing media structures and their change, communication and mediation processes in the media, effects on voting behaviour and party strategies as well as the development of innovative models and frameworks in various ICT sectors. The interdepartmental working group, a platform for inter- and transdisciplinary media research at the University of Innsbruck, held a lecture series on "Media and Minorities" in the winter semester 2010/2011 and also held a Media Day at the University of Innsbruck on the same topic. Most of the lectures held in this context are published in this anthology. The contributions show in an exemplary way the connections between media offers, technologies and institutions as well as minorities. - Der interdisziplinäre Forschungsbereich innsbruck media studies an der Universität Innsbruck zielt auf das Verstehen, Erklären und Gestalten von Strukturen der Medien und deren Wandel, Kommunikations- und Vermittlungsprozesse in den Medien, Auswirkungen auf Wahlverhalten und Parteienstrategien sowie auf die Entwicklung innovativer Modelle und Frameworks in diversen IKT-Sektoren. Die interfakultäre Arbeitsgruppe, eine Plattform für die inter- und transdisziplinär ausgerichtete Medienforschung an der Universität Innsbruck, hat im Wintersemester 2010/2011 eine Ringvorlesung zum Thema "Medien und Minderheiten" abgehalten sowie einen Medientag der Universität Innsbruck zum selben Thema durchgeführt. Die meisten der in diesem Rahmen gehaltenen Vorlesungen sind in diesem Sammelband vereint. Dabei weisen die Beiträge in exemplarischer Weise auf, welche Zusammenhänge zwischen Medienangeboten, -technologien und -institutionen sowie Minderheiten bestehen.